Reconstrução imediata de diferentes defeitos peri-implantares em implantes pós-exodônticos: análise histomorfométrica em cães - Pereira, Flávia Priscila [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Objective: The purpose of these studies were to evaluate bone regeneration at natural or surgically-created buccal defects at implants placed immediately into extraction sockets (IPIES). Material and methods: Eight Labrador dogswere used and implants were placed immediately into the extraction sockets of P2 (second premolar ) and M1 (first molar), bilaterally. At P2, the buccal wall of the extraction sockets was removed bilaterally to create a standardized defect, 4 mm wide coronally, 2 mm wide apically, and 6 mm height. At P2 sites, Bio-Oss at the test (OB) or autogenous bone at the control (OA) sites were used to fill the defects. At M1 sites, Bone Ceramic ® at the test (BC) or the clot alone (COA) were used to fill the defects. All surgical sites were subsequently covered by a resorbable collagen membraneand a non-submerged healing was allowed . After 4 months the animals were euthanized, bone blocks harvested and processed for histomorphometric analysis . Results: at P2 sites, IS- C values were slightly higher (2.3±0.8mm) in the OA compared to the OB (1.7±0.7 mm). IS- B were 2.7 ± 0.7mm and 2.2 ± 1.0mm on the buccal side and 1.6 ± 0.8mm and 0.8 ± 0.5mm on the lingual side at OA and OB groups, respectively. The average values of PM- C , B - PM and PM -IS in OA and OB groups were 4.3 ± 0.9mm , 4.7 ± 0.9mm , 2.0 ± 1.6mm and 4.3 ± 0.6mm , 4.8 ± 0.6mm , 2.5 ± 0.8mm, respectively. A statistically significant difference was only observed in the thickness of the buccal bony crest at 2-5 mm apically to IS (the implant neck) when the biomaterial (S -OCbt )...

Objetivo: A proposta deste estudo foi avaliar a regeneração óssea de defeitos criados cirurgicamente e naturais circunferenciais (gap) de implantes pósexodônticos. Materiais e método: Para este estudo foram utilizados 8 cães da raça labrador, nos quais foram instalados implantes imediatos (pós-exodônticos) nos alvéolos dos dentes P2 (2o pré-molar) e M1 (1o molar) inferiores bilaterais. Nos implantes da região dos 2º pré-molares bilaterais foram criados cirurgicamente defeitos peri-implantares vestibulares que foram preenchidos de um lado por osso autógeno – OA e do outro por osso bovino inorgânico Bio-Oss ®- OB. Nos alvéolos correspondentes aos primeiros molares (M1) os implantes foram instalados e os gaps (defeitos naturais) existente entre a tábua óssea vestibular e o implante, foram preenchidos por Bone Ceramic ® - (grupo BC) ou somente coágulo (grupo COA). Todos os sítios cirúrgicos foram posteriormente recobertos por membrana de colágeno reabsorvível (Biogide ®) e mantidos com cicatrizador. Após 4 meses de pós-operatório, os animais foram eutanasiados e os blocos ósseos processados laboratorialmente para análise histomorfométrica. Resultados: Os resultados obtidos nos implantes instalados na região do P2 mostraram que os valores do IS-C foram ligeiramente maior (2.3±0.8mm) no grupo OA, comparado ao grupo OB (1.7± 0.7 mm), enquanto o IS-B dos grupos OA e OB foram respectivamente de 2.7±0.7mm e 2.2±1.0 mm no lado vestibular e de 1.6±0.8mm e 0.8±0.5mm no lado lingual. As médias dos valores de PM-C, PM-B e PM-IS no grupo OA e OB foram respectivamente de 4.3±0.9mm, 4.7±0.9mm, 2.0±1.6mm e 4.3±0.6mm...
Keywords: Ossos - Regeneração; Osseointegração; Implantes dentários; Substitutos ósseos; Dental implants